Inventarisasi Jenis Ikan Air Tawar di Sungai Gajahwong Kabupaten Bantul - Budiantoro, Agung; Widyaningrum, Arista Suci; Suwartiningsih, Nurul (Jurnal Riset Daerah, 2021)
Abstract. Indonesia has a very high diversity of fish species. However, information on the richness of fish species in Indonesia is still limited. The Gajahwong River is one of the rivers with its upstream in Sleman Regency and the river flows through Yogyakarta Municipality and then through Bantul Regency and empties into the Opak River. The Gajahwong riverbank area is dominated by dense settlements and several factories so that household and factory waste dumped in the Gajahwong River has the potential to reduce its water quality. The purpose of this research was to determine the diversity of fish species found in the Gajahwong River, both native and introduced fish, and also to determine the abiotic environmental conditions. Sampling was done by means of purposive random sampling at three station points (I, II, and III) with each station divided into three sampling points. Measurement of the abiotic environmental parameters was carried out at each sampling point with three replications each. Fish samples were taken and identified. The results showed that there were 18 identified fish species, with details of which 13 were native to Indonesia and 5 (five) were introduced fish. The abiotic environmental parameters are in accordance with the water quality standards of class II-III, supporting the survival of fish in the Gajahwong river.